Reversed arthroscopic subacromial decompression for symptomatic irreparable rotator cuff tears: Mid-term follow-up results in 34 shoulders - Verhelst, Luk; Vandekerckhove, Pieter-Jan; Sergeant, Gregory; Liekens, Koen; Van Hoonacker, Petrus; Berghs, Bart (Journal of shoulder and elbow surgery, 2010)
In the elderly, there is no guideline for the treatment of irreparable rotator cuff lesions. The results of open or arthroscopic repair are variable. We hypothesized that the use of a reversed arthroscopic subacromial decompression (RASD) would yield comparable results. Between January 2004 and December 2006, thirty-eight patients underwent a RASD for irreparable cuff tears in 39 shoulders. The surgical procedure consisted of a tenotomy of the long head of the biceps tendon, a debridement of the torn rotator cuff and a tuberoplasty, without violation of the coracoacromial arch and the acromion. Thirty-three patients (age 69.9 ± 7.3 years) were available for clinical and radiological evaluation of 34 shoulders (male/female ratio: 11/22), at a mean follow-up of 38 months (range: 21 months–52 months). Two of 33 patients had required revision surgery, and were excluded from further statistical analysis. In the remaining 31 patients (32 shoulders), the modified Constant-Murley score (CMS) improved from 34.9% ± 11.6 to 84.0% ± 11.6 (p < 0.0001). The preoperative mobility did not correlate with the final result. Preoperative pain was found to correlate negatively to the modified CMS at follow-up (p= 0.0038). Although the acromiohumeral height decreased with 2.58 mm ± 1.68 and the severity of glenohumeral osteoarthritis increased with one grade (Samilson-Prieto classification), there was no correlation with the functional outcome. We conclude that for irreparable rotator cuff tears in the elderly, excellent mid-term results can be achieved with a RASD.